2009
DOI: 10.1164/rccm.200804-535oc
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Nrf2 in a Murine Model of Respiratory Syncytial Virus Disease

Abstract: Rationale: Respiratory syncytial virus (RSV) is the most frequent cause of significant lower respiratory illness in infants and young children, but its pathogenesis is not fully understood. The transcription factor Nrf 2 protects lungs from oxidative injury and inflammation via antioxidant response element (ARE)-mediated gene induction. Objectives: The current study was designed to determine the role of Nrf 2-mediated cytoprotective mechanisms in murine airway RSV disease. Methods: Nrf 2-deficient (Nrf 2 2/2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
182
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(203 citation statements)
references
References 62 publications
16
182
0
5
Order By: Relevance
“…In airways, PPARg agonists modulated nicotinamide adenine dinucleotide phosphate hydrogen oxidase and reduced reactive oxygen species production of asthmatic mice (60,80). Because murine Nrf2 is known to contribute to the pulmonary protection from allergy, sepsis, emphysema, ALI-ARDS, viral infection, or fibrosis, and PPARg has shown defensive roles in these disease models (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), it is hypothesized that PPARg-and Nrf2- mediated molecular events are closely associated in airway protection against oxidants. Supporting this concept, ALI induced by carrageenin was exacerbated in Nrf2 2/2 mice relative to Nrf2 1/1 mice, and administration of 15d-PGJ 2 reversed the augmented airway inflammation and protein hyperpermeability in Nrf2 1/1 mice caused by a cyclooxygenase-2 inhibitor, which led to depletion of lung 15d-PGJ 2 and Nrf2-dependent antioxidants (81).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In airways, PPARg agonists modulated nicotinamide adenine dinucleotide phosphate hydrogen oxidase and reduced reactive oxygen species production of asthmatic mice (60,80). Because murine Nrf2 is known to contribute to the pulmonary protection from allergy, sepsis, emphysema, ALI-ARDS, viral infection, or fibrosis, and PPARg has shown defensive roles in these disease models (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), it is hypothesized that PPARg-and Nrf2- mediated molecular events are closely associated in airway protection against oxidants. Supporting this concept, ALI induced by carrageenin was exacerbated in Nrf2 2/2 mice relative to Nrf2 1/1 mice, and administration of 15d-PGJ 2 reversed the augmented airway inflammation and protein hyperpermeability in Nrf2 1/1 mice caused by a cyclooxygenase-2 inhibitor, which led to depletion of lung 15d-PGJ 2 and Nrf2-dependent antioxidants (81).…”
Section: Discussionmentioning
confidence: 99%
“…Using mice genetically deficient in Nrf2 (Nrf2 2/2 ), a protective role for the Nrf2-ARE pathway has been demonstrated in oxidantmediated inflammatory lung injury including hyperoxia toxicity (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). To elucidate molecular mechanisms underlying Nrf2-mediated pulmonary protection against O 2 , we profiled Nrf2-dependent genes regulated during the development of hyperoxia-induced lung injury in Nrf2 1/1 and Nrf2 2/2 mice (17).…”
mentioning
confidence: 99%
“…SFN has been shown to be protective in vivo against pulmonary inflammation induced by respiratory syncytial virus (RSV) infection. Only Nrf2 +/+ mice given SFN, but not Nrf2 −/− given SFN, had a significant decrease in the number of neutrophils and eosinophils recruited to the lung after RSV challenge (Cho et al, 2009). SFN has also been shown to protect arterial endothelial cells in vivo from expressing a pro-inflammatory state, which was dependent on NRF2 (Zakkar et al, 2009).…”
Section: Nrf2mentioning
confidence: 99%
“…Sulforaphane pretreated nasal epithelial cells during influenza virus infection showed significantly increased levels of Nrf2 and HO-1 associated with reduced hemagglutinin gene expression and viral replication [39]. In a model of RSV infection, mice treated with sulforaphane showed significantly reduced numbers of neutrophils and eosinophils in BAL after infection [69], suggesting that this compound has the potential for modulating viral-induced oxidative stress and disease.…”
Section: Thiol Antioxidants Pyrrodolinedithiocarbonate (Pdtc)mentioning
confidence: 99%
“…Nrf2-dependent AOE gene expression might be reduced by: (i) competition for binding to the ARE site -Bach1/small Maf protein complex or AP-1 family transcription factors like c-Fos and FRA1 can bind to ARE acting as a transcriptional repressor [67,68]; (ii) preventing Nrf2 activation through direct physical association -Activating transcription factor (ATF)3 or retinoic acid receptor α were shown to form inhibitory complexes with Nrf2, leading to displacement from ARE elements; (iii) interfering with recruitment of co activators, such as CBP, to the ARE site -NF-κB activation can lead to decreased availability of CBP and promote the recruitment of co repressors (histone deacetylases) at Nrf2-ARE site [67]; (iv) reduced nuclear levels, which can occur due to enhanced nuclear to cytoplasm efflux or increased Nrf2 degradation [8]. A recent study has shown that RSV infection in Nrf2-/-mice is more severe and associated with higher viral titers, augmented inflammation, enhanced mucus production and epithelial injury compared to Nrf2 wild type mice, indicating the protective role of Nrf2-ARE pathway against RSV infection [69]. RSV infection can indeed induced a progressive decrease in ARE-dependent gene transcription in A549 cells, carcinoma-derived type II-like airway epithelial cells, investigated using luciferase reporter gene assays ( Figure 1A, left panel) [47].…”
Section: Potential Regulatory Mechanism Of Aoe Expression In Rsv Infementioning
confidence: 99%